Factors influencing the degree of smallholder farmer’s market participation : the case study of uMkhanyakude and Zululand districts, KwaZulu Natal Province of South Africa - Mashaya, Rufaro Talent (Stellenbosch : Stellenbosch University, 2021)
Thesis (MCom)--Stellenbosch University, 2021.